Nightblind - Ragnar Jónasson, 1976- (Ragnar Jónasson, 1976- Dark Iceland series., 2017)
"Chilling, and complex, Nightblind is an extraordinary thriller from undeniable new talent Ragnar Jonasson. Ari Thór Arason: a local policeman, whose tumultuous past and uneasy relationships with the villagers in an idyllically quiet fishing village in Northern Iceland--where no one locks their doors--continue to haunt him. The peace of this close-knit community is shattered by the murder of a policeman--shot at point-blank range in the dead of night in a deserted house. With a killer on the loose and the dark arctic winter closing in, it falls to Ari Thór to piece together a puzzle that involves tangled local politics, a compromised new mayor, and a psychiatric ward in Reykjavik where someone is being held against their will. Then a mysterious young woman moves to the area, on the run from something she dares not reveal, and it becomes all too clear that tragic events from the past are weaving a sinister spell that may threaten them all."--